1985
DOI: 10.1148/radiology.156.2.2989972
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct necrosis: complication of transcatheter hepatic arterial embolization.

Abstract: Bile duct necrosis because of transcatheter hepatic arterial embolization (THAE) in two patients with hepatocellular carcinoma is reported. Preoperative THAE was performed on 29 patients, and bile duct necrosis was experienced by two of the 29 (7%). In these two patients, gelatin (Gelfoam) powder was used as the embolus. Among the 24 whose embolus was clear, four were embolized with gelatin powder. Therefore, incidence of bile duct necrosis after THAE with gelatin powder was 50%. Because of the hazards of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(49 citation statements)
references
References 0 publications
0
47
1
1
Order By: Relevance
“…Portal blood flow is maintained during embolization of the hepatic artery with Gel foam, and normally, serious complications due to ischemia do not develop, because collateral vessels are formed at an early stage (8). However, it should be clearly understood that the infusion of embolic materials consisting of smaller particles, such as Gel foam powder, silicone, or iodized oil may fill the sinusoids, and then reflux into the portal vein, possibly inducing severe ischemia (6)(7)(8). This is especially likely to happen when the catheter is wedgedinto the hepatic artery, or transcatheter arterial embolization is carried out repeatedly within a short period of time (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portal blood flow is maintained during embolization of the hepatic artery with Gel foam, and normally, serious complications due to ischemia do not develop, because collateral vessels are formed at an early stage (8). However, it should be clearly understood that the infusion of embolic materials consisting of smaller particles, such as Gel foam powder, silicone, or iodized oil may fill the sinusoids, and then reflux into the portal vein, possibly inducing severe ischemia (6)(7)(8). This is especially likely to happen when the catheter is wedgedinto the hepatic artery, or transcatheter arterial embolization is carried out repeatedly within a short period of time (3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bilomas of iatrogenic origin after transcatheter arterial embolization have been reported (2,3). The small-diameter embolic material sometimes used in transcatheter arterial embolization may cause destruction of the wall of the bile duct by obstructing the peribiliary arterial plexus of the duct, resulting in leakage and subsequent pooling of the bile (4)(5)(6)(7). This is frequently preceded by hepatic infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Gelfoam powder should be not be used as this may cause biliary damage. 314 The procedure requires the advancement of the catheter into the hepatic artery and then to lobar and segmental branches aiming to be as selective as possible so as to induce only minimal injury to the surrounding non-tumorous liver. Multifocal HCC involving both hepatic lobes may require the obstruction of the total hepatic artery blood flow.…”
Section: Transarterial Embolization and Chemoembolizationmentioning
confidence: 99%
“…Hepatic artery obstruction is usually achieved by Gelfoam particles, but polyvinyl alcohol, starch microspheres, metallic coils, and autologous blood clots have also been used [321]. Gelfoam powder should not be used because this may cause biliary damage [323]. In a recent study, TACE performed with drug-eluting beads loaded with doxorubicin has been shown to modify the pharmacokinetics of the injected chemotherapy, thus reducing the drug-related adverse effects while maintaining the same therapeutic efficacy as TACE [324].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%